Effect of feed supplemented with a probiotic mixture on the productive parameters of Cavia porcellus, cuy. - Andía Ayme, Vidalina (2021)
The main objective was to evaluate the effect of feed supplemented with a probiotic mixture in the improvement of the productive parameters of Cavia porcellus, guinea pig. Thirty-six male kits weaned at 14 ± 2 days of age used for which the random design with four treatments, three repetitions and three animals per pool used. The averages subjected to the Tukey contrast test. The treatments were T0 as control, T1 50 ml, T2 100 ml and T3 150 ml of the probiotic mixture, respectively. Probiotics provided on a daily basis, mixing with the balanced food. The parameters evaluated were weight gain, feed intake in dry matter, feed conversion and carcass performance. The results showed that the inclusion of a probiotic mixture of Lactobacillus acidophilus, L. casei and Saccharomyces cerevisiae in guinea pig, feeding had a significant effect (p <0.05) on feed consumption and carcass performance. There were no significant differences for weight gain and feed conversion. However, numerically in all treatments with doses of the probiotic mixture, it exceeded the control; it also allowed reaching the commercial weight of the guinea pig at eight weeks.